Genetic engineering represents a safe approach for innovations improving nutritional contents of major food crops - Werner Arber (Journal of Innovation & Knowledge (JIK), 2017)
About 70 years ago early microbial genetic research revealed that inherited phenotypic traits become determined by DNA filaments composed of 4 different nucleotides that are linearly arranged. In the meantime we know that genes, the determinants of specific life functions, are genomic segments of an average size of about 1000 nucleotides, i.e. a very small part of a genome. Fundamental insights into the structures and functions of selected genes can be reached by sorting out the relevant short DNA segment, splicing this fragment into a natural gene vector such as a viral genome or a fertility plasmid. This allows the researchers to transfer the genetic hybrid into an appropriate host cell in order to produce many copies that can then serve for functional and structural analysis. This research approach became efficient in the 1970s. On the request of involved researchers, safety guidelines became proposed 1975 at the Asilomar Conference on Recombinant DNA (Berg, Baltimore, Brenner, Roblin, & Singer, 1975), then generally introduced and still largely followed nowadays. Carefully carried out genetic engineering by horizontally transferring a selected and functionally well known DNA segment into the genome of another organism has in many published biosafety investigations never shown any unexpected harmful effect. We will present below selected examples of research contributions enabling innovations for the benefit of human life conditions.
Keywords: L65; 650; Genetic engineering; Hunger; Biotechnology; Genetically modified (GM)